Implementasi Kebijakan Pemberian Bantuan Biaya Pendidikan : Studi Pada Peraturan Bupati Blitar Nomor 149 Tahun 2022 Tentang Pedoman Pemberian Bantuan Biaya Pendidikan Bagi Mahasiswa Berprestasi Atau Kurang Mampu - Ditya Nuryanuarifa; Wydha Mustika Maharani; Ulva Roifatul Lailin (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
The quality of human resources is a crucial foundation for improving the standard of living and the welfare of society. One indicator of human resource quality is the average level of education completed, and Indonesia has a low education level. The Blitar Regency Government is committed to addressing this issue by providing educational assistance in accordance with Blitar Regent Regulation Number 149 of 2022. This study aims to understand the process of implementing the educational assistance program policy and the factors influencing it, using the Van Meter and Van Horn model. The research was conducted at the Secretariat of Blitar Regency using a qualitative method through observation, interviews, and documentation. The results of the study show that the program implementation aligns with the policy, although there are obstacles in the variables of resources and inter-organizational communication. The main supporting factors are clear objectives and the commitment of the implementing agents.